Reduction reactions at the interface between CdS quantum dot and Z-type ligands driven by electron injection in the electroluminescent processes - Huo, Xiangyu (2024)
The efficient and stable electroluminescence of quantum dots (QDs) is of great importance in their applications in new display technologies. The short service life of blue QDs, however, hinders their development and commercialization. Different mechanisms have been proposed for the destabilization of QDs in electroluminescent processes. Based on real-time time-dependent density functional theory studies on the QD models covered by Z-type ligands (XAc2, X = Cd, Zn, Mg), the structural evolution is simulated to reveal the mechanism of the reduction reactions induced by electron injection. Our simulations reproduce the experimental observations that the reduction reactions occur at the QD-ligand interface, and the reduced Cd atom is almost in a zero valence state. However, different sites are predicted for the reactions in which the surface metal atom of the QD instead of the metal atom in the ligands is reduced. As a result, one of the arms of the chelate ligand leaves the QD, which tends to cause damage to its electroluminescent performance. Our findings contribute to a mechanistic understanding of the reduction reactions that occurred at the QD-ligand interface.